Long-Term Outcome of En Bloc Extensive Resection of the Penis and Prepuce Associated with a Permanent Perineal Urethrostomy in a Gelding Affected by Squamous Cell Carcinoma - Paola Straticò; Vincenzo Varasano; Gianluca Celani; Riccardo Suriano; Lucio Petrizzi (Case Reports in Veterinary Medicine)
A 15-year-old gelding was referred for a florid, cauliflower-like ulcerated mass, enclosing penis and prepuce together with penile urethra showing a malodorous purulent and blood-stained discharge and larvae infestation. En bloc extensive resection of the penis and prepuce, without penile retroversion or pexy to ventral abdomen associated with a permanent perineal urethrostomy, was performed. Histology of the mass revealed a squamous cell carcinoma of penis and prepuce. The surgical technique that was adopted is a modified version of that already described that allows a more proximal resection of the penile body and is a valid option for treating advanced SCC lesions involving the penis. Early postsurgical complications (mild strangury, haemorrhage from the urethrostomy site and its partial dehiscence, and infection of the abdominal wound) were managed with a medical treatment and resolved within 5 to 12 days. Three years after surgery the horse is in good body condition and does not show any sign of recurrence or disorders related to the surgery.